2008
DOI: 10.1113/jphysiol.2007.144113
|View full text |Cite
|
Sign up to set email alerts
|

Exercise intensity‐dependent contribution of β‐adrenergic receptor‐mediated vasodilatation in hypoxic humans

Abstract: We previously reported that hypoxia-mediated reductions in α-adrenoceptor sensitivity do not explain the augmented vasodilatation during hypoxic exercise, suggesting an enhanced vasodilator signal. We hypothesized that β-adrenoceptor activation contributes to augmented hypoxic exercise vasodilatation. Fourteen subjects (age: 29 ± 2 years) breathed hypoxic gas to titrate arterial O 2 saturation (pulse oximetry) to 80%, while remaining normocapnic via a rebreath system. Brachial artery and antecubital vein cathe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
94
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(99 citation statements)
references
References 34 publications
(57 reference statements)
5
94
0
Order By: Relevance
“…Adenosine appears to contribute only during hypoperfusion (75,83). ␤-Adrenergic receptor mechanisms appear to contribute during lower intensity hypoxic exercise (509), but much of this contribution is likely due to ␤-adrenergic-mediated NO release (73,117). This response again highlights the general observation that many dilator substances involved in exercise hyperemia have effects both on vascular smooth muscle and the vascular endothelium.…”
Section: O Blood-borne Vasodilator Substancesmentioning
confidence: 91%
See 1 more Smart Citation
“…Adenosine appears to contribute only during hypoperfusion (75,83). ␤-Adrenergic receptor mechanisms appear to contribute during lower intensity hypoxic exercise (509), but much of this contribution is likely due to ␤-adrenergic-mediated NO release (73,117). This response again highlights the general observation that many dilator substances involved in exercise hyperemia have effects both on vascular smooth muscle and the vascular endothelium.…”
Section: O Blood-borne Vasodilator Substancesmentioning
confidence: 91%
“…As discussed earlier, muscle blood flow is augmented during exercise under hypoxic conditions. This augmentation occurs despite an increase in sympathetic vasoconstrictor activity directed at the skeletal muscle (196), which is capable of restraining the increase in blood flow to the contracting muscle during hypoxia (456,509). So there is competition between hypoxic dilation and sympathetic constriction and evidence that hypoxia can attenuate vasoconstrictor responses to sympathetic nerve activation and exogenous norepinephrine in resting skeletal muscle of animals and humans (48,205,206).…”
Section: B Contraction Blunts Sympathetic Vasoconstrictionmentioning
confidence: 99%
“…A self-regulating partial rebreathe system that clamps end-tidal CO2 at baseline levels despite large changes in minute ventilation was used to generate hypoxic conditions (1,29,31,32). The target arterial O 2 saturation (SO2; assessed via pulse oximetry) was ϳ80%.…”
Section: Systemic Hypoxiamentioning
confidence: 99%
“…Previous studies have demonstrated that ␤-adrenergic receptor activation is responsible for a substantial portion of the hypoxic vasodilation at rest (2,29,31) and during mild forearm exercise (31). However, the ␤-adrenergic component of the compensatory vasodilation decreases with increased exercise intensity.…”
mentioning
confidence: 99%
See 1 more Smart Citation